2015
DOI: 10.1590/0103-8478cr20141391
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of biodegradable film based on zein and oleic acid added with nanocarbonate

Abstract: Zein oleic acid films added with 1, 2 and 3% (w/w) of

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(4 citation statements)
references
References 4 publications
(1 reference statement)
0
4
0
Order By: Relevance
“…In this case, the values did not exceed the elongation of the control zein film. The usual trend was confirmed that a less rigid structure with lower tensile strength was associated with increased material elasticity and vice versa, which as shown by comparing Figure 1 a,b [ 12 ]. The lower plasticizing activity of thyme oil could be ascribed to phenolic–phenolic interactions between thymol molecules, which are predominant in this type of essential oil [ 8 , 12 ].…”
Section: Resultsmentioning
confidence: 67%
See 1 more Smart Citation
“…In this case, the values did not exceed the elongation of the control zein film. The usual trend was confirmed that a less rigid structure with lower tensile strength was associated with increased material elasticity and vice versa, which as shown by comparing Figure 1 a,b [ 12 ]. The lower plasticizing activity of thyme oil could be ascribed to phenolic–phenolic interactions between thymol molecules, which are predominant in this type of essential oil [ 8 , 12 ].…”
Section: Resultsmentioning
confidence: 67%
“…While the PEG plasticization effect was poor in pure zein films due to their low compatibility, the same plasticizer caused a more significant increase in elongation in composite films based on zein and methyl cellulose. Incorporating nanocarbonate in the concentrations from 1 to 3 wt% ensured the higher flexibility of zein oleic acid films [ 12 ].…”
Section: Discussionmentioning
confidence: 99%
“…It has been used to develop functional biodegradable packaging [5] , packages with antimicrobial agents [6][7][8][9] , packaging for periodontal biomaterials and substrates for cell culture [10] . Studies with zein have been carried out in respect to the regeneration of osseous tissues [11] , with nanoparticles used to improve the mechanical properties of films [12,13] and edible film to increase the shelf life of pears [14] and macadamia [15] .…”
Section: Introductionmentioning
confidence: 99%
“…Zein films can be obtained by processing in devices such as kneading, blowing and/or extrusion machines [7][8][9] . Plasticizers such as glycerol, polyols and fatty acids are added during the formation of zein films to improve film flexibility and manageability, since pure zein films are usually very brittle and fragile [10][11][12] . Glycerol is considered a secondary plasticizer for zein and, when used alone, its effect is limited due to its incompatibility with zein [13] .…”
Section: Introductionmentioning
confidence: 99%